2006
DOI: 10.1111/j.1600-051x.2006.01035.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological outcomes of quadrant versus full‐mouth root planing as monitored by real‐time PCR

Abstract: The results of the present study showed similar microbiological outcomes following both treatment modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 37 publications
3
42
1
1
Order By: Relevance
“…Jervøe-Storm et al 7 showed similar levels of Aggregatibacter actinomycetemcomitans, F. nucleatum ssp., P. gingivalis, Prevotella intermedia, T. denticola and T. forsythia following the FMSRP and PMSRP approaches up to six months. Similar results were also demonstrated for the levels of A. actinomycetemcomitans, P. gingivalis, P. intermedia, Dialister pneumosintes, Campylobacter rectus and Parvimonas micra at eight months after both therapies.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Jervøe-Storm et al 7 showed similar levels of Aggregatibacter actinomycetemcomitans, F. nucleatum ssp., P. gingivalis, Prevotella intermedia, T. denticola and T. forsythia following the FMSRP and PMSRP approaches up to six months. Similar results were also demonstrated for the levels of A. actinomycetemcomitans, P. gingivalis, P. intermedia, Dialister pneumosintes, Campylobacter rectus and Parvimonas micra at eight months after both therapies.…”
Section: Discussionmentioning
confidence: 97%
“…However, the authors provided only a short-term evaluation (4-6 weeks) after treatments. 18 It should be noted that the current and all of the above-mentioned studies (Quirynen et al, 4 Apatzidou et al, 5 Koshy et al, 6 Jervøe-Storm et al, 7 Swierkot et al, 8 Zijnge et al, 9 Lang et al, 11 Serrano et al 18 ) verified that the subgingival microbiota improved significantly from baseline to post-therapy evaluations for both the FMSRP and PMSRP approaches. In fact, it is well documented that the proportions of periodontal pathogens are found at higher levels before than after SRP in subjects or at sites that responded clinically well, since positive microbiological changes must precede clinical improvements.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations